Volatile Oil Components of Laurel (Laurus nobilis L.) Leaves Obtained from Plants Cultivated under Salinity Stress Conditions - Amina Ben Ayed; Giampaolo Zanin; Echrak Aissa; Faouzi Haouala (Horticulturae, 2022)
Laurel (Laurus nobilis L.) is a strict endemic species of natural vegetation of the Mediterranean region, which is known for its medicinal, aromatic, forestry, ornamental and culinary properties. This species produces valuable essential oil (EO). The content of EO and its composition depend on different factors, e.g., genetic, cultural practices and environmental conditions. Among these, salt stress is a major limiting factor, which affects almost all plant functions. Similar to essential oils (EOs), biotic and abiotic stresses may stimulate or inhibit the emission of volatile compounds (VCs) in plant materials, suggesting that these substances can be responsible on stress defense strategies. Therefore, an experiment was conducted to assess the effect of different NaCl concentrations (0, 50, 100 and 150 mM) of the irrigation water on VCs of laurel leaves. Our results showed that salt stress affected the volatile metabolites compounds, mainly the major ones. For instance, 1,8-cineole and linalool were negatively affected by high salinity levels, while the opposite was observed for α-terpenyl acetate and methyl eugenol. The proportion of grouped compounds of laurel VCs also differed among the studied treatments. The relative content of oxygenated monoterpenes and monoterpene hydrocarbons, respectively the first and the second largest groups, decreased with increasing NaCl concentration. Differently, the relative amount of sesquiterpene hydrocarbon group increased, especially at 100 mM NaCl. These findings indicate that the cultivation of laurel in marginal lands, characterized by high salinity or low-quality water, must be carefully evaluated because it significantly varies the quality of its products.